A Review on the Drip Irrigation System of Greenhouse Crops in Cambodia - Chea Mengponleu; Serey Mardy (International Journal of Sustainable Applied Sciences, 2023)
Drip irrigation systems provide the most water efficiency in the dry season in Cambodia. In Agriculture 4.0, MAFF signed an MoU with a private company to build 10,000 greenhouses to supply 400 tons of crops annually. The objective of this review paper is to synthesize the literature on drip irrigation of greenhouse crops and the benefits of drip irrigation in greenhouses. Drip irrigation enables us to: reduce the impact of drought and climate change on food production; avoid contamination of groundwater and rivers caused by fertilizer leaching; support rural communities, reduce poverty, and reduce migration to cities. Moreover, it has the highest water efficiency in the dry season. In greenhouses, water and fertilizer usage efficiency is improved in the rainy seasons by using plastic covers on the roof. Therefore, Agriculture 4.0, combined with drip irrigation and greenhouses, helps farmers grow crops throughout the year. Farmers' knowledge should be upgraded in using, maintaining, and repairing both drip irrigation systems and greenhouses.